Extension services in Rwanda take up the volunteer farmer trainer approach - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
The East Africa Dairy Development program successfully used the volunteer farmer trainer (VFT) approach in Kenya, Rwanda, and Uganda. PIM-supported research on the VFT approach was in part responsible for its uptake by 21 development organizations in Rwanda. Three years after the end of the EADD program in Rwanda, VFTs are still training farmers with support from the government, NGOs, and producer organizations.